Generation of temperature anisotropy for alpha particle velocity distributions in solar wind at 0.3 AU: Vlasov simulations and Helios observations. Issue 4 (25th April 2014) - Perrone, D.; Bourouaine, S.; Valentini, F.; Marsch, E.; Veltri, P.
<x xml:space="preserve">Abstract</x> Solar wind "in situ" measurements from the Helios spacecraft in regions of the Heliosphere close to the Sun (∼0.3 AU), at which typical values of the proton plasma beta are observed to be lower than unity, show that the alpha particle distribution functions depart from the equilibrium Maxwellian configuration, displaying significant elongations in the direction perpendicular to the background magnetic field. In the present work, we made use of multi‐ion hybrid Vlasov‐Maxwell simulations to provide theoretical support and interpretation to the empirical evidences above. Our numerical results show that, at variance with the case of βp≃1 discussed in Perrone et al. (2011), for βp=0.1 the turbulent cascade in the direction parallel to the ambient magnetic field is not efficient in transferring energy toward scales shorter than the proton inertial length. Moreover, our numerical analysis provides new insights for the theoretical interpretation of the empirical evidences obtained from the Helios spacecraft, concerning the generation of temperature anisotropy in the particle velocity distributions.